Study of Soil Degradation Status at Jatipurno District, Keduang Sub-Watersheds, Wonogiri Regency, Central Java - Apriani Widiatiningsih; Mujiyo Mujiyo; Suntoro Suntoro (Universitas Sebelas Maret, 2018)
This study is aimed to evaluate soil degradation based on Standard Criteria of Soil Degradation for Biomass Production under Indonesian Government Regulation No. 150 in 2000. Conducted at Jatipurno District, Keduang Sub-Watersheds, between October and December 2016, at seven selected land units, each land unit is represented by four sample points. The selection of sampling area is according to Stratified Purposive Sampling method. The evaluation of soil degradation is carried out by determining the threshold value and key factors of soil characteristics based on the Standard Criteria of Soil (matching process), which lead to degradation. The results showed that the entire soil at Jatipurno District is slightly degraded. The most extensive soil degradation 2,869.31 ha area (69.60%) is caused by a low colloid fraction, high bulk density, low total porosity and low soil permeability. The soil degradation mostly caused by low soil permeability which the number is under critical threshold < 0.7 cm hour-1 in the entire land units. Implementing providing organic matter to the soil, planting variations of cover crops, on land plots (low, medium, high cover crops), land management by crop rotation and intercropping, minimum tillage in accordance with the rules of environmental conservation, can be done to minimize the soil degradation.